ANALISIS DAMPAK MUATAN SEMEN TERHADAP KESEHATAN AWAK KAPAL PADA PROSES CLEANING PALKA DI KM. TONASA LINE XII - Muhammad Adnan Nugraha; Hadi Setiawan; Indra Farman (STKIP Subang, 2026)
This study aims to analyze the factors causing health problems among ship crew during the cargo hold cleaning process on KM Tonasa Line XII using a qualitative descriptive method through observation and interviews. The results show that although the work implementation has followed established procedures, there are still health risks due to exposure to cement dust. The cleaning process, which is carried out manually, along with the enclosed, hot conditions of the cargo hold and limited ventilation, increases the concentration of dust in the air. The impacts experienced by the crew include respiratory disorders, eye and skin irritation, and physical fatigue. The use of personal protective equipment (PPE) is not yet optimal due to limited availability, inadequate condition, and discomfort during use. In addition, the lack of supervision and training affects the low level of awareness and compliance in using PPE. Fishbone analysis identifies six main contributing factors: human, work methods, equipment, materials, environment, and management. Control measures include improving discipline in PPE usage, optimizing the use of dust collectors, improving ventilation systems, and conducting regular safety training to minimize health risks among the crew.